Effect of organic acids on the preservation and feeding value reconstituted milo - Bolsen, K.K.; Cox, O.J.; Drake, C.L. (Kansas State University. Agricultural Experiment Station, 2011)
The use of high moisture grain in beef cattle rations has increased during the past several years. It has improved feed efficiency of high energy rations five to 20 percent in previous research. Non-nutritional advantages of high moisture grain include: (1) earlier harvest to lengthen the harvest season and/or free land for other uses; (2) fewer field losses from shattering lodging, wind and early frost and (3) no artificial drying.
Keywords: Beef; Organic acids; Milo; Feed value